2009
DOI: 10.3324/haematol.2009.015024
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous presentation of ALK-positive anaplastic large cell lymphoma following insect bites: evidence for an association in five cases

Abstract: BackgroundSkin involvement is frequent in ALK-positive anaplastic large cell lymphomas. The role of an insect bite as a triggering event has been postulated but not well documented. Design and MethodsWe retrospectively investigated five cases of ALK-positive anaplastic large cell lymphoma who presented with skin lesions occurring after an insect bite. Biopsies were immunostained with antibodies against CD30, ALK, T-and B-cell antigens. ResultsPersistent skin lesions developed after solitary insect bites in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
2
43
1
1
Order By: Relevance
“…Lamant et al 29 recently reported 5 children with systemic ALK + ALCL that presented as skin lesions at the site of preceding insect bites, often with involvement of the draining local lymphnode. Thus, the skin might not only present a preferred microenvironment for ALK + ALCL but might even be the primary site of lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lamant et al 29 recently reported 5 children with systemic ALK + ALCL that presented as skin lesions at the site of preceding insect bites, often with involvement of the draining local lymphnode. Thus, the skin might not only present a preferred microenvironment for ALK + ALCL but might even be the primary site of lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A single ALK lesion, although essential for transformation, requires additional genetic defects, which are however yet to be determined. The actual impact of insect bites in the pathogenesis of ALK C ALCL remains to be elucidated (Fornari et al 2009, Lamant et al 2010.…”
Section: Alk Fusion Proteinsmentioning
confidence: 99%
“…4 The subsequent release of cytokines leading to skin inflammation at the site of the bite could act as a "second hit" eliciting activation of T lymphocytes, which would then express the oncogenic NPM-ALK protein and undergo uncontrolled proliferation and transformation. 4 ALK ϩ ALCL patients also present with an inflammatory syndrome characterized by high fever, lymphadenopathy or neutrophilia, release of various circulating inflammatory chemokines such as IL-8, 5 and expression of skin-inflammatory biomarkers such as the alarmins heat-shock protein 90 (HSP90), HSP70, 6 S100A8, or A11. 7 Recent studies have highlighted a role for IL-8 in mediating cutaneous skin inflammation and human keratinocyte hyperplasia associated with acanthosis (thickening of the skin).…”
Section: Introductionmentioning
confidence: 99%
“…Our group reported 5 cases of systemic ALK ϩ ALCL in which skin lesions presented after an insect bite at the onset of the disease, postulating that bite-associated Ags could result in an influx of T lymphocytes, some of them bearing the t(2;5) translocation. 4 The subsequent release of cytokines leading to skin inflammation at the site of the bite could act as a "second hit" eliciting activation of T lymphocytes, which would then express the oncogenic NPM-ALK protein and undergo uncontrolled proliferation and transformation. 4 ALK ϩ ALCL patients also present with an inflammatory syndrome characterized by high fever, lymphadenopathy or neutrophilia, release of various circulating inflammatory chemokines such as IL-8, 5 and expression of skin-inflammatory biomarkers such as the alarmins heat-shock protein 90 (HSP90), HSP70, 6 S100A8, or A11.…”
mentioning
confidence: 99%